SAT0244 PROGNOSIS OF LARGE VESSEL INVOLVEMENT IN LARGE VESSEL VASCULITIS. (2nd June 2020) - Vautier, M.; Dupont, A.; De Boysson, H.; Comarmond, C.; Mirault, T.; Mekinian, A.; Lambert, M.; Ferfar, Y.; Aouba, A.; Cacoub, P.; Resche-Rigon, M.; Saadoun, D.
Abstract : Background: Giant cell arteritis (GCA) and Takayasu arteritis (TAK) are the two main forms of large vessels vasculitis (LVV). Vessel inflammation leads to aneurysms, wall thickening, stenosis, and, in some cases, complete occlusion of the artery. Due to the wide variation in the course of LVV, predicting outcome is challenging. To our knowledge, data regarding prognosis factors of LVI in LVV patients and comparison of outcome of LVI in GCA and TAK are lacking. An early identification of patients with higher mortality could help to prevent deaths and vascular complications. Objectives: To assess prognosis factors and outcome of large vessel involvement (LVI) in large vessels vasculitis (LVV) patients. Methods: Retrospective multicenter study of characteristics and outcomes of 417 patients with LVI including 299 Takayasu arteritis (TAK) and 118 Giant cell arteritis (GCA-LVI) were analyzed. Logistic regression analysis assessed prognosis factors in LVV patients. Outcome of LVI among TAK and GCA-LVI patients (ischemic complications, aneurysms complications, relapses and revascularization) were assessed. Results: In multivariable analysis, stroke/transient ischemic attack [HR: 3.63 (1.46 - 9.04), p=0.006] was independently associated with vascular complications in LVV. The 10-years aneurysm free survival was significantly lower [67% (48 – 93) vs 89% (84 – 95), p=0.02] in GCA-LVI compare to TAK patients. The 5-years relapse free survival was significantly lower [47% (37 – 60) vs 69% (63 – 75), p<0.001, ] in GCA-LVI compare to TAK patients. The 10-years revascularization free survival was significantly lower [55% (48 – 64) vs 76% (59 – 99), p<0.001] in TAK compare to GCA-LVI patients. After a median follow-up of 5 years, 16 (5.4%) TAK and 7 (5.9%) GCA-LVI patients died, mainly of aneurysm (26%) and ischemic complications (26%). Conclusion: This large nationwide cohort of LVI provided prognosis factors of vascular complications in LVV patients. TAK and GCA-LVI have different long-term outcome in term of aneurysm development, relapse and revascularization. Disclosure of Interests: None declared